ESTIMATION OF PHENOLIC AND FLAVONOIDS CONTENT AND IN VITRO ANTIOXIDANT CAPACITY OF TRIDEX PROCUMBENS LINN.(ASTERACEAE). - ABRAR HUSSAIN MIR; MANJUSHA SEXENA; MOHD YOUSUF MALLA (International Journal of Pharma and Bio Sciences, 2013)
It consists of dried wholes plants of Tridax procumbens Linn. belonging to family Asteraceae. Aim of Study: The present Study was undertaken to investigate the Total Phenolic Content was estimated by Folin-Ciocaltea Method with an absorbance peak at 765nm using Spectrophotometer and will be expressed as Gallic Acid Equivalents (GAE) in milligram per gram of extract (mg GAE/g extract), Total Flavonoid Content with an absorbance peak at 510nm using spectrophotometer and can be expressed in milligrams of Rutin equivalents (RE) per gram of extract. And most importantly the antioxidant capacity of crude extract of Tridex procumbens Linn. using DPPH (1, 1- Diphenyl-2-picrylhydroxyl) assay and Hydrogen peroxide (H2O2) scavenging assay. The antioxidant activities were compared to standard antioxidant ascorbic acid. Ascorbic acid is a naturally occurring antioxidant compound found in medicinal plants, vegetables, fruits and whole grains. Methanolic crude extract of the plant Tridex procumbens Linn. showed significant antioxidant activity in DPPH, H2O2 scavenging methods. The findings of the present study suggested that the plant could be a potential natural source of antioxidants and could have greater importance as therapeutic agents in preventing or slowing oxidative stress related degenerative diseases.